Antiubiquitin antibody in localised and systemic scleroderma. Issue 6 (June 1996) - Fujimoto, M; Sato, S; Ihn, H; Kikuchi, K; Tamaki, T; Tamaki, K; Takehara, K
Abstract : OBJECTIVE: To determine the presence of antiubiquitin antibody (AUbA) in localised scleroderma and systemic sclerosis, as it is frequently found in the sera of patients with systemic lupus erythematosus (SLE) and has also been shown to have a close relationship with antihistone antibodies that have an important role in scleroderma. METHODS: Serum samples from patients with localised scleroderma (n = 48) and systemic sclerosis (n = 52) were examined by enzyme linked immunosorbent assay. Twenty samples from patients with SLE, 20 from patients with dermatomyositis, and 30 samples from healthy individuals were used as controls. RESULTS: AUbA was demonstrated in 44% of patients with localised scleroderma and in 42% of those with systemic sclerosis. The presence of AUbA correlated with the presence of antihistone antibodies in both localised scleroderma and systemic sclerosis. CONCLUSIONS: AUbA is frequently present in patients with localised scleroderma and systemic sclerosis. Induction of AUbA is closely associated with that of antihistone antibodies, suggesting that ubiquitinated histone may be the target in autoimmune responses of these disorders.